The Influence of Cultural Values on the Eating Habits and Dietary Patterns of IPB University Students - Syahrul Rahmadani; Aurellita Putri Asha; Luthfi Shatara Harriendyo; Adithra Artiearvira; Tsabita Aulia Putri (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
This study aims to explore the influence of cultural values on the eating habits of Program Pendidikan Kompetensi Umum IPB University students, representing the younger generation in a multicultural and globalized context. Employing a nutritional anthropology approach and qualitative methods through observation and in-depth interviews with students from diverse cultural backgrounds the research finds that food functions not only as a biological need but also as a marker of identity and cultural heritage. Family upbringing and pride in traditional cuisine are key factors influencing students’ food preferences. Despite living in a dynamic and modern academic environment, many students continue to maintain their regional dietary practices as a form of emotional connection and cultural preservation. The findings suggest that student eating patterns result from a complex interaction between culture, self-identity, and social surroundings. Therefore, nutrition intervention programs in university settings should be designed with cultural sensitivity. Providing healthy food options inspired by regional flavors and involving families in nutrition education can promote more sustainable and culturally rooted eating habits.